Becoming Helen Keller [videorecording (DVD)] - Crowley, John, 1942-; Murphy, Mary McDonagh; Alexander, Rebecca (Psychotherapist); Jones, Cherry; Snipe, Warren; Wailes, Alexandria (PBS, 2021)
Helen Keller, who was deaf and blind since early childhood, was a passionate advocate for change, using her celebrity and wit to champion rights for women, people with disabilities, and people living in poverty. Becoming Helen Keller examines the complex legacy of this author, advocate, lecturer, and human rights pioneer.